Preface: phys. stat. sol. (b) 242/9 - Sánchez, Maria (physica status solidi (b), 2005)
The XVII Latin American Symposium on Solid State Physics took place in the conference rooms of the Convent San Francisco de Asis, in the heart of the Old Havana. The sixteen previous editions were organized in eight different countries; the last two were in Colombia (Cartagena, 1999) and Venezuela (Merida, 2002). After eighteen years the meeting came back to Havana in 2004. The program topics included: Surfaces and interfaces analysis; Spintronics; Magnetism; Materials and energy; Ab‐initio methods, simulations and modeling in solids; Nanophysics, nanomaterials and nanotechnology; New materials, properties and applications; Preparation of materials, thin films and characterization; High temperature superconductivity; Techniques of structural analysis in solids. The program included 6 plenary talks, 13 invited talks, 58 oral presentations (in eight sessions) and 200 poster contributions (in four poster sessions). The meeting attracted more than 200 participants from 14 countries. The physica status solidi Young Researcher Award sponsored by Wiley‐VCH was conferred at the meeting. This prize was divided between two participants: Clara Calderón (“Study of electrical transport properties of ZnO thin films used as front contact of solar cells”) from Colombia and Aimé Pelaiz Barranco (“AC behavior in lanthanum modified PZT ferroelectric ceramics”) from Cuba. Special Mentions went to Valérie Halté (“Femtosec‐ond dynamics of transmission of gold arrays of sub‐wavelength holes”) from France, Erick Larramendi Cancio (“Cd desorption induced by Zn exposure during atomic layer epitaxy of CdxZn1−xTe”) and Julio Cesar Rimada Herrera (“Quantum and conversion efficiency calculation of AlGaAs/GaAs multiple quantum well solar cells”) from Cuba. Nanostructures and in general low dimensional physics related to different systems was a very hot topic during the meeting. Some talks and presentations were devoted to optoelectronic materials and devices. Characterization of solids by different structural and optical techniques together with modeling and simulations were also important subjects of the symposium. The XVIII Symposium will be held in Mexico in 2006. The editors wish to thank all the participants who contributed to the success of the meeting and hope that it helped to develop close links between researchers and institutions of Latin America. (© 2005 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)